World Development Indicators 2017 - World Bank (Washington, DC, 2017)
This year the World Development Indicators database has been improved to include more indicators that cover the Sustainable Development Goals and more data disaggregated by sex, age, wealth quintile, and urban or rural location. New data include access to clean cooking fuels and the number of industrial design applications registered globally. This edition reflects two major structural changes to World Development Indicators: • Poverty and shared prosperity, previously part of World view, is now a standalone section. Global highlights presented in World view encompass data from all six thematic sections. • Data on the Sustainable Development Goals are now presented in a new companion publication, Atlas of Sustainable Development Goals 2017, which analyzes and visualizes World Development Indicators data to explore progress toward the goals for 2030 and catalyzes discussion of measurement issues and data needs.